ANALISIS STABILITAS SOIL NAILING SEBAGAI ALTERNATIF PENANGANAN LONGSOR DI JALUR NASIONAL PIKET NOL LUMAJANG JAWA TIMUR - Muhammad Fahmi Ibrahim; Paksitya Purnama Putra; Indra Nurtjahjaningtyas (Direktorat Bina Teknik Jalan dan Jembatan, 2021)
The Piket Nol national route is an alternative route across the southern island of Java that connects the Lumajang Regency with the Malang Regency. Landslide-prone areas are starting from KM Turen 53 to KM Turen 59 on this route. The Simplified Bishop method is used in analyzing slope stability and modeling soil nailing reinforcement with numerical modeling. Slope and soil nailing stability control are applied following SNI 8460 2017. The average value of the safety factor for the natural slope's stability at the top of the road is 0.269 or less than 1.07 (unstable). Whereas the stability of the lower slope of the road in most locations shows a stable condition (SF>1.25), except for KM 57+100, KM 58+100, and KM 58+900 with an average SF value of 1,183 (critical). The average value of the safety factor for the top slope stability after reinforcement using soil nailing is 1,728, whereas for the lower slope stability is 1,853. Soil nailing is designed as slope improvement at KM 57+900, other than that in anticipation of the potential for landslides at KM 56+900-KM 57+700 and KM 58+100-KM 59+100. The results of all stability control of slope reinforcement using soil nailing have met the SNI 8460 2017 criteria. Therefore, soil nailing can be an alternative solution in dealing or anticipating with landslides on The Piket Nol national route. Key words: landslide, slope stability, safety factor, soil nailing, soil nailing stability.